RESPON PEMBERIAN MOL (MIKRO ORGANISME LOKAL ) REBUNG BAMBU TERHADAP PERTUMBUHAN CABAI RAWIT (Capsicum frutescens L.) DI MEDIA GAMBUT - Novilda Elizabeth Mustamu (JURNAL AGROPLASMA, 2019)
The study aimed to determine the response of giving MOL (Micro Local Organisms) to the growth of cayenne pepper (Capsicum frutescensL.) On peat media. The research was carried out in the villages of Sempurna, Aek Tapa, Rantauprapat, North Sumatra at the beginning of April to July 2018. The materials used for conducting the research were cayenne seeds, peat soil, bamboo shoot MOL, polybags, water. The tools used for the research are hoes, machetes, ropes, meters, scissors, saws, knives, liters and writing instruments. This study used a Randomized Block Design (RBD) method with one factorial. This research was divided into 4 treatments which were repeated 10 times, namely: M0: Control, M1: Giving MOL as much as 1 liter / repeat, M2: Giving MOL as much as 1.5 liters / repetition, M3: Giving MOL as much as 2 liters / repetition. Micro Application of Local Organisms Bamboo shoots can increase the growth of cayenne. Giving Micro Bamboo 1 Local Organisms 1 liters gives a good response to the high growth of chili plants with the highest achievement of 1.98 cm difference. Giving Micro Bamboo Local Organisms 1 liters bamboo shoots gave a good response to the stem diameter of cayenne pepper with the highest achievement of the highest difference of 2.80 mm. Giving Micro Local Organisms bamboo shoots 2 liters give a good response to the number of leaves of cayenne pepper with the achievement of the highest difference of 13 strands. Keywords: bamboo shoots, Cayenne pepper, Local microorganisms, peat soil